Voluntary running influences the efficacy of fluoxetine in a model of postpartum depression. (January 2018) - Gobinath, Aarthi R.; Richardson, Robin J.; Chow, Carmen; Workman, Joanna L.; Lieblich, Stephanie E.; Barr, Alasdair M.; Galea, Liisa A.M.
Abstract: Postpartum depression affects approximately 15% of mothers. Unfortunately, treatment options for postpartum depression are limited. Pharmacological antidepressants such as fluoxetine (FLX) can be controversial due to inconclusive evidence of efficacy during the postpartum and concerns of neonatal exposure to antidepressants. Alternatively, non-pharmacological antidepressants such as exercise may be less controversial but its efficacy in postpartum depression is unclear. To investigate this, we treated rat dams daily with high levels of corticosterone (CORT; 40 mg/kg), to induce a depressive-like phenotype, or oil (vehicle for CORT) during the postpartum period. Within the oil and CORT conditions, four additional antidepressant conditions were created: 1. FLX (10 mg/kg) + exercise (voluntary access to running wheel); 2. FLX + no exercise; 3. Saline (vehicle for FLX) + exercise; 4. Saline + No exercise. We examined maternal care, depressive-like and anxiety-like behavior, stress reactivity, and hippocampal neurogenesis and dams were categorized as "high running" or "low running." FLX treatment, alone or with high running, prevented CORT-induced disruptions in maternal care. As expected, CORT increased depressive-like behavior but exercise, regardless of running amount, reduced depressive-like behavior. Intriguingly, FLX, but not CORT, increased anxiety-like behavior, which was not mitigated by concurrent exercise. FLX treatment slightly but significantly facilitated serum CORT recovery after forced swim stress. CORT and FLX alone reduced neurogenesis, while exercise coupled with FLX increased density of doublecortin-expressing cells. High running increased density of doublecortin-expressing cells (immature neurons) in comparison to controls. Collectively, these findings indicate that FLX and exercise reverse different endophenotypes of depression in dams, which has translational implications for surveying treatment options of postpartum depression. Highlights: Postpartum CORT (corticosterone) reduced maternal care and hippocampal neurogenesis. Postpartum fluoxetine (FLX) prevented CORT-induced reductions in maternal care. Exercise, but not FLX, reduced CORT-induced maternal depressive-like behavior. FLX increased neurogenesis in dams only in combination with exercise.